STREET CHILDREN'S LEGAL PROTECTION IN BANDUNG DISTRICT - Hardi Fardiansyah; Rio Christiawan; Tuti Widyaningrum (Pusat Riset dan Inovasi Nasional, 2023)
The lowest echelons of society have been affected by the global spread of the coronavirus epidemic, which has infected people from all walks of life and altered regional lives and cultural practices. In addition to causing a recession in the national economy, this issue has also decreased peoples' purchasing power and ability to withstand the rising cost of living.This study outlines the efforts made by the Bandung Regency government to provide good guarantees for street children through preventive measures, financial education assistance, fostering enthusiasm and shelter supervision, developing regulations and policies, and providing freedom of choice for street children in the medium term through playing, direct support, approaches to tackling social issues, and suggestions for revenue management. the enhancement of human resources, research into the growth of street children, and evaluation of good street child conduct are all attempts to better society.The problem is that because of spiritual issues, many of them try to escape and destroy necessities of life. Despite having a sizable state budget, it is impossible to employ street children in suitable jobs. Additionally, there is still a dearth of assistance and backing from many organizations.